2021
DOI: 10.1002/vetr.560
|View full text |Cite
|
Sign up to set email alerts
|

In vivo three‐dimensional isometry analysis of suture attachment sites for extracapsular suture stabilization of the canine stifle

Abstract: Background The study aimed to perform isometry analysis of a selection of suture attachment points for extracapsular stabilization with three‐dimensional (3D) measurements and normal gait kinematics of the stifle joint. Methods Thirteen client‐owned dogs were recruited. Fluoroscopic images of the stifle during treadmill walking and computed tomography of the same joint were acquired. Stifle kinematics were reconstructed using 3D model‐based fluoroscopic analysis. Variability of the distance between the femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several preceding studies have revealed notable cranial tibial subluxation after CCLD progression [ 1 3 , 24 , 28 30 ], but only a few studies have assessed and compared the CTT between different pairs of quasi-IPs [ 19 , 24 , 31 , 32 ]. It is expected that suturing at different positions affects the resistance capability in tibial cranial translation, as sutures with alignment closer to the craniocaudal direction can contribute a greater tensile force component to counteract tibial cranial translational forces [ 12 ]. However, only a few studies reported that suturing at T1 was found to be more effective in resisting CTT than suturing at T2 or T3 [ 19 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several preceding studies have revealed notable cranial tibial subluxation after CCLD progression [ 1 3 , 24 , 28 30 ], but only a few studies have assessed and compared the CTT between different pairs of quasi-IPs [ 19 , 24 , 31 , 32 ]. It is expected that suturing at different positions affects the resistance capability in tibial cranial translation, as sutures with alignment closer to the craniocaudal direction can contribute a greater tensile force component to counteract tibial cranial translational forces [ 12 ]. However, only a few studies reported that suturing at T1 was found to be more effective in resisting CTT than suturing at T2 or T3 [ 19 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the suggestions in previous studies [ 12 , 20 ], at the lateral condyle of the femur, the point distal to the lateral femoral fabella (F2) was chosen for the suture attachment site. The site was paired with the point located approximately 4–5 mm caudal to the insertion point of the patellar ligament (equivalent to T1 in Hulse et al [ 20 ] and referred to as ECS-IP1 in the present study, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To build statistical shape models (SSMs) for the femur and tibia, the training dataset was created by retrospectively collecting CT data from our former studies 17 19 . This dataset comprised CT data from a total of 40 dogs, with an average body weight of 22.7 ± 4.6 kg and an age of 3.6 ± 1.7 years.…”
Section: Methodsmentioning
confidence: 99%